Monitoring of complement activation biomarkers and eculizumab in complement‐mediated renal disorders. (25th November 2016) - Wehling, C.; Amon, O.; Bommer, M.; Hoppe, B.; Kentouche, K.; Schalk, G.; Weimer, R.; Wiesener, M.; Hohenstein, B.; Tönshoff, B.; Büscher, R.; Fehrenbach, H.; et al.
Summary: Various complement‐mediated renal disorders are treated currently with the complement inhibitor eculizumab. By blocking the cleavage of C5, this monoclonal antibody prevents cell damage caused by complement‐mediated inflammation. We included 23 patients with atypical haemolytic uraemic syndrome (aHUS, n = 12), C3 glomerulopathies (C3G, n = 9) and acute antibody‐mediated renal graft rejection (AMR, n = 2), treated with eculizumab in 12 hospitals in Germany. We explored the course of complement activation biomarkers and the benefit of therapeutic drug monitoring of eculizumab. Complement activation was assessed by analysing the haemolytic complement function of the classical (CH50) and the alternative pathway (APH50), C3 and the activation products C3d, C5a and sC5b‐9 prior to, 3 and 6 months after eculizumab treatment. Eculizumab concentrations were determined by a newly established specific enzyme‐linked immunosorbent assay (ELISA). Serum eculizumab concentrations up to 1082 μg/ml point to drug accumulation, especially in paediatric patients. Loss of the therapeutic antibody via urine with concentrations up to 56 μg/ml correlated with proteinuria. In aHUS patients, effective complement inhibition was demonstrated by significant reductions of CH50, APH50, C3d and sC5b‐9 levels, whereas C5a levels were only reduced significantly after 6 months' treatment. C3G patients presented increased C3d and consistently low C3 levels, reflecting ongoing complement activation and consumption at the C3 level, despite eculizumab treatment. A comprehensive complement analysis together with drug monitoring is required to distinguish mode of complement activation and efficacy of eculizumab treatment in distinct renal disorders. Accumulation of the anti‐C5 antibody points to the need for a patient‐orientated tailored therapy. Abstract : Analysis of complement activation biomarkers prior to, 3 and 6 months after eculizumab treatment in 23 patients treated with eculizumab for atypical hemolytic uremic syndrome (aHUS, n=12), C3 glomerulopathies (C3G, n=9) or acute antibody‐mediated renal graft rejection (AMR, n=2) indicate effective inhibition in aHUS and AMR patients, whereas increased C3d and consistently low C3 levels reflect ongoing complement activation in C3G patients. Therapeutic drug monitoring, performed by a newly established specific ELISA, revealed serum eculizumab concentrations up to 1082 μg/mL pointing to drug accumulation especially in pediatric patients, which indicates the need of a patient‐oriented tailored therapy.